Built to Last Designing a Flexible and Durable 2015 Climate Change Agreement - Briner, Gregory (OECD/IEA Climate Change Expert Group Papers, 2014)
The aim of this paper is to explore what a flexible and durable 2015 climate change agreement could look like and propose pragmatic options for the design of such an agreement. A durable 2015 climate change agreement would continue to be ambitious, fair and effective in 2020 and beyond. An agreement that is designed to be durable could also help to encourage widespread participation by governments, as well as improve the credibility of the agreement for investors. To achieve these objectives, a degree of flexibility could be included in the mitigation and other provisions of the 2015 agreement. If so, a balance may need to be struck between (i) providing enough flexibility for countries to feel comfortable participating in the agreement, (ii) providing predictability regarding the provisions of the agreement and the actions that governments intend to take, and (iii) the collective level of ambition of the agreement. Success will be needed on all fronts if the agreement is to be durable. Building some flexibility into the design of the 2015 agreement could make it more durable in the face of new scientific discoveries, external changes and shocks, as well as evolving country circumstances. The focus of this paper is on the mitigation part of the 2015 agreement. The paper outlines possible processes for consultations and updating of mitigation contributions. It also discusses the possible structure of the 2015 agreement and the implications of different mitigation contribution types for the flexibility and durability of the agreement